2008
DOI: 10.1007/s11524-008-9302-y
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Racial/Ethnic Concentration, Social Disadvantage, and Homicide Risk: An Ecological Analysis of 10 U.S. Cities

Abstract: Homicide is one of the leading causes of death among African-American and Hispanic men. We investigated how neighborhood characteristics associated with social disadvantage explain racial/ethnic homicide gaps in 10 U.S. cities. The test hypotheses were that (1) higher concentrations of African-Americans and Hispanics would be associated with higher homicide rates and (2) the relationship between racial/ethnic concentration and homicide would be attenuated after adjusting for neighborhood characteristics (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…However there were in general a large proportion of homicide victims who were socially disadvantaged with a history of chronic abuse. This has also been noted by other researchers [7,[10][11][12]. This knowledge has important implications for homicide prevention, and bringing sociopolitical strategies into focus.…”
Section: Discussionsupporting
confidence: 68%
“…However there were in general a large proportion of homicide victims who were socially disadvantaged with a history of chronic abuse. This has also been noted by other researchers [7,[10][11][12]. This knowledge has important implications for homicide prevention, and bringing sociopolitical strategies into focus.…”
Section: Discussionsupporting
confidence: 68%
“…However, studies measuring heterogeneity have shown conflicting results with regard to homicide rates (Strom & MacDonald, 2007;Wang & Arnold, 2008). In contrast, studies focusing on neighborhood racial or ethnic concentration, such as the percent Black or Hispanic residents, have found a strong positive relationship between this measure and rates of homicide (Jones-Webb & Wall, 2008;Krueger, Bond Huie, Rogers, & Hummer, 2004). Research also shows that the association between neighborhood racial or ethnic composition and homicide is largely accounted for by structural conditions of concentrated economic deprivation and social isolation (Jones-Webb & Wall, 2008;McCall et al, 2010;Vélez, Krivo, & Peterson, 2003).…”
Section: Racial Concentrationmentioning
confidence: 99%
“…12 Individuals living in disadvantaged neighborhoods often work in low wage jobs with less autonomy and control over their work, and problem drinking might be less tolerated in such work environments. 61 Because crime rates are higher in disadvantaged neighborhoods than in more affluent neighborhoods, [62][63][64][65] individuals living in disadvantaged neighborhoods are also more likely to come in contact with local police. This is particularly true for African Americans who are about one and half times (1.4) times more likely than their White peers to be detained by the police.…”
Section: Path Analysesmentioning
confidence: 99%